Lung function measurements in traditional bakers - Patouchas, D.; Efremidis, G.; Karkoulias, K.; Zoumbos, et al., N. (Acta Biomedica Atenei Parmensis, 2008)
Background: Respiratory disease is common and amenable to early detection and management in the primary care setting. Spirometric and phlethysmographic evaluation of ventilatory function plays a critical role in the diagnosis, differentiation and management of respiratory illness such as asthma, chronic obstructive pulmonary disease and restrictive disorders. Methods: Study subjects consisted of 58 workers in the production of bread and 45 salesclerks of bread from the same bakeries. The lung function of employees was checked using a spirometry and body phlethysmography, calculating the indexes Forced expiratory volume 1 sec (FEV1), forced vital capacity (FVC), FEV1/FVC ratio, residual volume (RV), total lung capacity (TLC), and RV/TLC ratio. The percentage of the obstructive and the restrictive impairment both in the bread producers and sellers was also searched as well as the percentage of response in the bronchodilation. Results: Bread producers recorded significantly lower mean lung functions compared with salesclerks, for FEV1, FVC and FEV1/FVC ratio, when observed values were expressed as percentages of predicted normal values. Furthermore the percentage of obstructive impairment among the bread producers was 12, 6%, while a percentage of 20, 68% of them presented a response in bronchodilation (while the percentage in salesclerks was 6, 6% respectively). The percentage of restrictive impairment was similar in both groups (12, 6% for bread producers and 11, 1% for salesclerks). Conclusion: The study concluded that bread producers in traditional bakeries in Greece are at increased risk of developing airway obstruction compared with salesclerks of bread from the same bakeries. A different degree of smoking status and of wheat flour dust exposure may explain this difference. Technical preventive measures such as well ventilated work areas and appropriate respiratory protective devices should be adopted.